The Role of Gratitude for Organizational Citizenship Behavior (OCB) in Employees - Nida Hasanati; Shabiq Anisa (Analitika: Jurnal Magister Psikologi UMA, 2023)
The existence of employees for the organization is crucial for the fulfillment of organizational goals. Employees who voluntarily work more than expected will be able achieve these goals, with the gratitude they have. This study aims to see the role of gratitude on Organizational Citizenship Behavior (OCB), using quantitative correlational method. The study was conducted on 150 employees of Kediri District Health Office. This study uses simple regression analysis hypothesis testing. The results showed a positive effect of gratitude on OCB of 12.2%. Points to, the higher employee's gratitude, the higher their OCB and vice versa. Moreover, 87.8% of OCB employees are affected by other factors. This research aims as a reference for HRD, employees, and employees to increase the effectiveness of tasks completion to achieve joint goals.